Two new species of Graffenrieda (Melastomataceae: Merianieae) from Colombia and Panama - Almeda, Frank; Marcela, Alvear; Mendoza, Humberto (Phytotaxa, 2014)
Two new species of Graffenrieda (Melastomataceae: Merianieae) are described from Colombia and Panama. Graffenrieda jefensis, a Panamanian endemic from Cerro Jefe, is characterized by a calyptrate calyx that falls away as a unit at anthesis, 5-merous flowers, 3-locular ovary, and conspicuous persistent calyx teeth. Graffenrieda maklenkensis, a Colombian endemic from the Cordillera Oriental in the northern Andes of Colombia, has a calyx that is fused in bud but ruptures into four (rarely three) lobes at anthesis that lack external calyx teeth, 4-(5)-merous flowers, a 3-(4)-locular ovary, and hypanthial indumentum (at anthesis) that is minutely lepidote intermixed with glandlike or resinous scurfy trichomes. Each species is illustrated, compared with presumed relatives, and provided with a conservation assessment using IUCN guidelines.